Adherence to Phosphodiesterase Type 5 Inhibitors in the Treatment of Erectile Dysfunction in Long‐Term Users: How Do Men Use the Inhibitors?. Issue 2 (27th May 2014) - Carvalheira, Ana; Forjaz, Vera; Pereira, Nuno Monteiro
Abstract Introduction The high effectiveness of phosphodiesterase type 5 inhibitors (PDE5‐i) in the treatment of erectile dysfunction (ED) has been demonstrated. However, previous research shows that PDE5‐i treatments have high discontinuation rates. Aim The main goals of this study were to (i) characterize the way men use PDE5‐i and (ii) analyze the adherence to treatment, identifying the factors that influence PDE5‐i use. Methods A total of 148 men with clinical diagnosis for ED who maintained the treatment with PDE5‐i for over 3 years were interviewed. Interviews concerning their ongoing treatment were carried out using a standardized questionnaire with quantitative and qualitative items. Main Outcome Measures Physiological measures included the intracavernous alprostadil injection test, associated with penile rigidometry and penile Doppler ultrasound. The qualitative measure included two questions: "Do you use the drug in every sexual intercourse?" and "How do you use the inhibitor?" Results ED causes were classified as venogenic (31%), arteriogenic (23%), psychogenic (18%), iatrogenic (13%), neurogenic (8%), and diabetic (7%). Participation rate was 71.8%. Of the 148 patients studied, 75% claimed not to use PDE5‐i in every intercourse. Most used tadalafil (66%), followed by sildenafil (20%), vardenafil (10%), and 4% alternated the type of medicine. Four main categories emerged concerning the factors that determine the intake of PDE5‐i in some intercourse situations and not in others: (i) psychological factors; (ii) medication‐related factors; (iii) circumstantial factors; and (iv) relational factors. Conclusion The analysis of men's narratives revealed a combination of factors that influence the adherence to PDE5‐i. The psychological and medication‐related factors were the most prevalent. This study highlighted the importance of taking these factors into account, both at the time of prescription and during the follow‐up in order to improve adherence. Carvalheira A, Forjaz V, and Pereira NM. Adherence to phosphodiesterase type 5 inhibitors in the treatment of erectile dysfunction in long‐term users: How do men use the inhibitors? Sex Med 2014;2:96–102.